Polish artists in Kazakhstan: with love to the steppe: Польские художники в Казахстане: с любовью к степи - Shaygozova, Zhanerke; Sultanowa, Madina (Przegląd Wschodnioeuropejski, 2021)
The article analyzes the cultural and creative heritage of artists of Polish descent who found themselves in Kazakhstan for various reasons in the period from the middle of the 19th to the end of the 20th centuries. In addition to their unconditional artistic value, the results of their creative efforts are of great scientific importance for modern Kazakhstan as unique ethnographic sources and documentary evidence of the daily graft and life of the Kazakh steppe. Domestic historical science already has a certain reserve dedicated to various sociopolitical, cultural and economic aspects of Kazakh-Polish relations, where the deportation of Poles and the formation of Kazakhstan’s Polonia are of particular importance. However, the creative heritage of Polish artists in Kazakhstan fell into the field of vision of scientists extremely occasionally. While its cultural and art historical context is able to shed light on many facets of the history, ethnography and culture of the Kazakh people. During the research, retrospective, comparative-historical and formal-stylistic campaigns were used. The result of the research is a retrospective analysis of the works of some of the most prominent Polish artists, due to various factors, for whom the Great Steppe has become not only a home, but also a source of inspiration and strength.